Thomas Willis: physician who described the circle of Willis, the arterial anastomosis at the base of the brain. (2nd February 2021) - Ellis, Harold
Abstract : Thomas Willis is known for the discovery and description of the circle of Willis, but his contributions to the development of medicine were much broader, including the first use of the term 'neurology'.